2000
DOI: 10.1093/jn/130.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Diamine Oxidase Activity Is Greater in Copper-Adequate than Copper-Marginal or Copper-Deficient Rats

Abstract: The object of this study was to determine whether serum diamine oxidase activity could distinguish among adequate, marginal and deficient copper status in rats. Male weanling Sprague-Dawley rats (n = 21) were randomly assigned to one of three dietary regimens, with copper concentrations of 0.52, 1.73 and 6.7 mg/kg diet. On completion of the study, body weights were significantly different among dietary groups, with copper-marginal rats displaying the highest mean weight and copper-deficient rats the lowest. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Normally, Ն95% of plasma Cu is ceruloplasmin bound, and levels of circulating Cu and ceruloplasmin are closely related (19). These are the biomarkers most frequently used as measures of Cu status, and both are depressed in severe Cu deficiency (20). However, levels plateau when Cu intake is adequate and do not reflect the magnitude of Cu intake beyond this point, so they are not useful for characterizing Cu excess states (21).…”
Section: Discussionmentioning
confidence: 99%
“…Normally, Ն95% of plasma Cu is ceruloplasmin bound, and levels of circulating Cu and ceruloplasmin are closely related (19). These are the biomarkers most frequently used as measures of Cu status, and both are depressed in severe Cu deficiency (20). However, levels plateau when Cu intake is adequate and do not reflect the magnitude of Cu intake beyond this point, so they are not useful for characterizing Cu excess states (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although, 0.7 mg of copper is significantly less copper than the control group received, it may have been enough to allow the rats to grow well for 60 days. However, the rats fed a copperdeficient diet were indeed copper-deficient, as indicated by both their decreased concentration of hepatic copper (Table 2) and their lack of p-phenylenediamine oxidase activity in their sera, which is a good indication of the copper status of the animals (Kehoe et al 2000), because the primary enzyme responsible for oxidizing p-phenylenediamine in serum is the coppercontaining enzyme ceruloplasmin (Ravin 1961).…”
Section: Discussionmentioning
confidence: 99%
“…Animal and human studies have shown that plasma diamine oxidase (DAO) activity is reduced in mild copper deficiency (4,5). However, tissue injury may also increase plasma DAO activity, thus confounding its interpretation.…”
Section: Assessment Of Copper Statusmentioning
confidence: 99%